IMPLEMENTASI PERATURAN WALIKOTA DENPASAR NOMOR 36 TAHUN 2018 TENTANG PENGURANGAN PENGGUNAAN KANTONG PLASTIK - Ni Nengah Karuniati; Noor Muhammad (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
The problem of plastic waste must be handled not only by the government but also by non-governmental organizations (NGOs) and the community. There are still many people who are using plastic bags in their daily lives. This lack of awareness of those people of reducing plastic bags is caused by; (a) Lack of social support that includes socio-cultural and community involvement to obey the rules, (b) lack of support from human and non-human resources, and (c) lack of support from the ability of executing agents – bureaucracy, norms and clear work patterns. Based on these facts, the research problem of this study is; how is the implementation of Denpasar Mayor Regulation Number 36 of 2018 on the use of plastic bags. This research was conducted qualitatively to determine and analyse the implementation of this regulation. Quantitative and qualitative data of this research were from primary and secondary data which were collected through observation, interviews, documentation, and from internet. Based on the theory of G. Shabbir Cheema and Dennis A. Rondinelli, there are four variables, namely condition of community environment, relationship between organizations, organizational resources for program implementation, and characteristics and capabilities of executing organization. The efforts and strategies that have been made by Denpasar City Government include among other things collecting data of the use of plastic bags, signing joint commitments, doing campaigns, arranging talk shows, and making policies one of which is Denpasar Mayor Regulation No. 36 of 2018.